PENGUATAN KAPASITAS EKONOMI PONDOK PESANTREN NURUL JADID MELALUI UNIT USAHA EN-JE MART - Agus Sulthoni Imami; Halimi Fauzen; Muhammad Mukhles (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2021)
Strengthening capacity is a demand for policies that will be taken in the process of improvement or change for individuals or institutions in achieving predetermined goals. Strengthening the capacity in the business will have a significant impact on the sustainability of the business being carried out. Nurul Jadid Islamic boarding school is one of the Islamic boarding schools which has significant influence on many aspects of community life. The existence of a pesantren business, namely EN-JE mart, is one of the income-generating business units for the pesantren. The results of the study obtained from this study include the strategies used by EN-JE mart to attract consumers, both in terms of improving the organizational structure, budget capacity, facilities and infrastructure, and services. By using descriptive qualitative research methods, the description obtained from the results of this study aims to provide insight and further assess the positive performance of EN-JE mart.